SARUSUN BERDASARKAN PPJB DENGAN PELAKU PEMBANGUNAN (STUDI PUTUSAN NOMOR 91/PDT/2020/PT YYK) - Wiwin Sumartini; Endang Pandamdari (Reformasi Hukum Trisakti, 2021)
Actors in the construction of flats can sell to buyers by marketing them first through the Binding Sale and Purchase Agreement (PPJB) system. In practice, development actors often do not comply with or violate the agreement of what was agreed in the PPJB. According to Law Number 20 of 2011 concerning Flats and what are the legal consequences of the Yogyakarta High Court decision Number 91/PDT/2020/PT YYK on control of flats based on PPJB, a study using normative juridical methods, the nature of the research is descriptive then the data used is secondary data, data analysis is done by qualitative analysis and conclusions are done deductively. This research resulted in an answer to the formulation of the problem, that is, to transfer ownership rights to an apartment unit, it must be carried out through a sale and purchase deed as the basis for the transfer of HMSRS in accordance with article 44 paragraph (1) of the Flats Law. The legal consequence of the Yogyakarta High Court Decision Number 91/PDT/2020 PT YYK is that the ownership rights to the Flats have not transferred ownership to the buyer.